Creative ecologies where thinking is a proper job - Howkins, John 1945- (Transaction Publishers, 2010)
In this book, the author identifies an ecology of thinking and learning based on how people create, develop and share ideas. It shows the conditions for successful thinking and learning, as well how we handle ideas and knowledge, both our own and other people's, and how this affects networks and markets.